Combinational Drug Therapy Induced Severe Hyponatremia in a Hypertensive Patient- A Case Report - Kavya, HB; Mustafa, Mohammed; KM, Ashamol; Kommeri, Hitha; Biju, Reya Merin (Journal of Pharmacy Practice and Community Medicine)
Hyponatremia, ranging from mild to severe and from asymptomatic to symptomatic, is a serious medical condition that requires immediate medical management. The frequent factors that precipitate hyponatremia include decreased intake of sodium, inappropriate secretion of antidiuretic hormone, and concurrent use of medications that impair water excretion. Weakness, nausea, vomiting, perplexity, dizziness, physical inactiveness, seizure, and coma are some of the often symptoms presented with hyponatremia. Discontinuing the offending agent and providing additional support is vital in restoring the serum sodium level. In this case report, a 63-year-old male patient was presented to the hospital with symptoms of giddiness, tremors, and 3-4 episodes of convulsion. He has a past history of diabetes and hypertension and is on regular medication. Laboratory findings showed the presence of hyponatremia with a serum Na+ value of 115mmol/l. On assessing this case, it is found that ARB/thiazide combination (telmisartan+chlorthalidone) has induced hyponatremia and is managed by treating with a hypertonic saline solution together with alteration of ARB/thiazide combination to calcium channel blocker. Gradually, the serum sodium level was normalized and the patient became stable.
Keywords: Combinational drug therapy; Angiotensin receptor blockers; Thiazide diuretics; Hyponatremia; Hypertension.